Drafting standards on cognitive accessibility: a global collaboration. - Steel, Emily J.; Janeslätt, Gunnel (Disability & Rehabilitation: Assistive Technology, 2017)
Purpose:The International Organization for Standardization (ISO) is working on accessibility of products to support people with cognitive impairment. Working Group 10, within the technical committee 173 (assistive products for persons with disability) was formed in 2014 to draft standards for assistive products that support people with cognitive impairment. Method:This article explains the scope and purpose of the working group and the context for its formation, and describes the plans and process for drafting and publishing new international standards. Results:The proposed suite of standards is presented, with examples from a draft standard on daily time management. It draws on international research evidence for the effectiveness of assistive products designed to support time management in people with cognitive impairment. Examples of assistive products and their key features are provided based on domains of time as defined in the International Classification of Functioning, Disability and Health for Children and Youth (ICF-CY). Conclusions:The proposed standards will provide design recommendations for features and functions that increase the accessibility of products used by people with cognitive impairment. They are intended to be used by designers, manufactures, educators and services providers, to facilitate their commitment to inclusion and demonstrate their willingness to work with accessibility regulation. Implications for RehabilitationNew standards based on universal design (UD) principles can guide the design of more user-friendly assistive products for people with cognitive impairment.Greater usability of assistive products, whether mainstream or specially-designed, will make it easier for practitioners to find and introduce assistive solutions to individuals with cognitive impairment.Greater usability of assistive products for daily time management can decrease the need for user training and support and enable participation.